2014
DOI: 10.2214/ajr.13.11490
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement for Detection of Malignant Features of Intraductal Papillary Mucinous Neoplasms of the Pancreas on MDCT

Abstract: OBJECTIVE The purpose of this retrospective study was to measure interobserver agreement in the assessment of malignant imaging features of intraductal papillary mucinous neoplasms (IPMNs) on MDCT. MATERIALS AND METHODS Pancreatic protocol CT studies were reviewed for 84 patients with resected IPMNs. Maximal diameter of the dominant cyst, presence of a mural nodule, presence of a solid component, and diameters of the main pancreatic duct (MPD) and common bile duct (CBD) were measured by four radiologists ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…A possible explanation may be the limitation of CT/MRI in identifying features associated with malignancy in BD-IPMNs, particularly mural nodules. 21 Interestingly, we observed that 28% of mural nodules detected by EUS were missed by CT/MRI in the malignant group; with cyst size ranging between 2.1-3.5 cm. Among the malignant mural nodules missed by CT/MRI (n=4), 2 did not have any WF.…”
Section: Discussionmentioning
confidence: 67%
“…A possible explanation may be the limitation of CT/MRI in identifying features associated with malignancy in BD-IPMNs, particularly mural nodules. 21 Interestingly, we observed that 28% of mural nodules detected by EUS were missed by CT/MRI in the malignant group; with cyst size ranging between 2.1-3.5 cm. Among the malignant mural nodules missed by CT/MRI (n=4), 2 did not have any WF.…”
Section: Discussionmentioning
confidence: 67%
“…28 This fact underlines the strength of MPD diameter in the diagnostic evaluation. Beyond MPD diameter, mural nodules and symptoms are identified as predictors of malignancy in IPMNs with main pancreatic duct involvement in the current literature.…”
Section: Discussionmentioning
confidence: 85%
“…These findings support the value of NGS, given that the preoperative diagnosis of pancreatic cysts can be quite challenging, especially in centers without significant experience. 18,[43][44][45][46] Biochemical and cytologic analysis are valuable ancillary tests of pancreatic cyst fluid; however, appropriate specimen handling (eg, maintaining the cyst fluid fresh without dilution) and routine triage of cyst fluid for biochemical analysis is not always performed. In addition, CEA levels are not always elevated in mucinous cysts as shown in a significant number of the mucinous cysts in this study, and various cut points in CEA level supportive of a mucinous cyst affect accuracy.…”
Section: Discussionmentioning
confidence: 99%